“Estrategias post Covid-19 para incrementar la afluencia de turistas en las hosterías de tres estrellas de la Parroquia Vilcabamba, del Cantón y Provincia de Loja” - Picoita Toledo, Diana Elizabeth (2021)
The parish Vilcabamba located to the south east of the province of Loja, known as The Valley of Longevity, has several natural and cultural tourist attractions, as well as a privileged climate, which have made it an important tourist destination of Ecuador, this being an important factor for several tourist establishments, mainly dedicated to providing the lodging service to their own and strangers, to be raised within the parish. However, the emergence of the Covid-19 pandemic, which originated at the end of 2019 and is characterized by its high level of contagion as it is a viral disease, therefore, all governments worldwide presented biosecurity measures to prevent such contagion being one of the main the social distancing and the use of masks, which is why this pandemic produced major changes and impacts on the tourism sector of this parish and the whole world, mainly to the establishments that provide the lodging service that for several months remained closed, which led to considerable economic losses. In view of the above, it was important to develop this research work, for which it was raised as a general objective: "To determine post Covid-19 strategies to increase the influx of tourists in the three-star inns of Vilcabamba Parish, canton and province of Loja"; three specific objectives were set to meet this objective; "To diagnose the current situation, with regard to the Covid-19 pandemic of the three-star inns of Vilcabamba parish, canton and province of Loja" for this purpose, the analytical method used to carry out an analysis of the current situation of the three-star inns of the parish Vilcabamba, which are part of the object of study, the inductive method to know the peculiarities of each of the inns with regard to the application of biosecurity protocols; also applied the techniques of direct observation, interview, survey, bibliographic review, the methodological models of the PESTEL analysis and the five forces of Porter, verification sheet for compliance with biosecurity measures developed from the biosecurity protocol for the reopening of tourist accommodation establishments proposed by the Ministry of Tourism (MINTUR) and the Data Sheet for the information collection of tourist establishments of MINTUR; developed the Strengths, Opportunities, Weaknesses and Threats Matrix (FODA) to determine the current situation of the inns under study; the second objective was also raised: "Propose post-Covid-19 strategies to increase the influx of tourists in the three-star inns of Vilcabamba Parish, canton and province of Loja" for which the synthetic method was used to determine what were the best post Covid strategies, taking into account biosecurity measures that guarantee greater security to guests, all this by developing strategic matrices that describe all the important aspects that must be taken into account before implementing each strategy, finally the third objective was raised "Socialize the results to the owners of the three-star inns of the parish Vilcabamba, canton and province of Loja" was used the technique of the Method of Rapid Analysis and Participatory Panification 5 (MARPP) the same that was developed in three phases , The first consisted of the delivery of a call to those involved in the proposal; the second where the results obtained were presented; and the third where the conclusions and recommendations of socialized work were recepted, as well as the implementation of surveys to assess the importance of the work presented. As a result of socialization, the acceptance of the proposed strategies by those involved for the resilience of pandemic effects on the tourism sector was determined. Finally, the following conclusions were raised: - The impact left by the health emergency has been largely negative for all sectors, however, it has also become an opportunity for innovation for tourism entrepreneurs to make an improved rethinking of their service. - The tourism and hotel sector have been cracked and due to the consequences left by the health emergency, despite this some companies have managed to stay afloat, offering and taking advantage of digital tools. - Vilcabamba being a parish whose main economic activity is tourism, has been affected on a large scale due to the impact generated by the pandemic, due to the restrictions of travelers. - The lodging sector has been the hardest hit during the pandemic, which is why according to the information obtained it can be evidenced that they only cover 40 percent of the total occupation. - The three-star inns that are providing the service have 83% percent of the biosecurity protocols implemented. - The reason why several lodging establishments did not reactivate the provision of their services is mainly due to the fear of contagion. - The proposed strategies will increase the influx of tourists in the lodging service during and after the pandemic. - The strategies socialized to those involved allow tore-jump the importance of these for the resilience of the tourism sector in the face of the pandemic. - There is no support from the parish GAD to counter the impacts of the pandemic on the tourism sector.